Energy generation from swine wastewater using microbial fuel cells. - Rafols, Caressa Ma. Krisel E
Microbial fuel cells (MFCs) are devices constructed from inexpensive materials that use microorganisms like bacteria as the catalysts to oxidize organic and inorganic matter and generate electricity. A two chambered MFC was used where there is an anode and cathode chamber. There were three treatments that were carried out. First, MFC with thirty percent swine wastewater (30 percent) were analyzed. Second was MFC with forty percent (40 percent) swine wastewater. The third treatment was MFC with fifty percent (50 percent) swine wastewater control, MFC with swine wastewater. Data were recorded and collected every day for 25 days for all three (3) treatments. The power density and the current density were then calculated for all treatments. The results of the present study show that MFC could be used to generate electricity using swine wastewater as a substrate. Further studies are needed to be conducted to realize the full potential of swine wastewater as fuel source for MFCs as well as to lessen its contribution to the wastes in the environment.